2011
DOI: 10.5603/fhc.2011.0060
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the content of lipids derived from the eye lenses of various species

Abstract: Abstract:Abstract: Abstract: Abstract: Abstract: The lipid content in the eye lens was analyzed and compared among various species in this study. The eye lens lipids of the following species were investigated: cow, horse, duck, and freshwater trout. Additionally, the lipids derived from cataractous bovine lens and from cataractous human eye lens lipoprotein complexes were analyzed. The following lipid classes were detected in clear lenses: cholesterol, sphingomyelin, phosphatidylcholine, phosphatidyletanolamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
(12 reference statements)
1
1
0
Order By: Relevance
“…Our study shows that PL composition of SF can markedly differ between these two mammalian species, a profile that has also been shown for plasma [40,41]. Differing PL profiles among vertebrates were also described for erythrocyte membranes and tissues such as the eye, heart and brain, all of which also depend on health status and differences in enzymatic activity [18,[40][41][42][43][44][45][46].…”
Section: Plos Onesupporting
confidence: 77%
“…Our study shows that PL composition of SF can markedly differ between these two mammalian species, a profile that has also been shown for plasma [40,41]. Differing PL profiles among vertebrates were also described for erythrocyte membranes and tissues such as the eye, heart and brain, all of which also depend on health status and differences in enzymatic activity [18,[40][41][42][43][44][45][46].…”
Section: Plos Onesupporting
confidence: 77%
“…On basis of the observations, it can be suggested that these fatty acids collectively or individually can act as biomarkers of aging lens. Since these fatty acids are present in the aging lens and three of them are known to have beneficial role, perhaps the ophthalmic preparations containing such substances could be good for keeping the lens healthy; however, it is necessary to check whether these fatty acids are also present in aging human lens since there are species variations in lens lipid composition [23].…”
Section: Discussionmentioning
confidence: 99%